Country size, specialization patterns and secular demand stagnation - Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2017)
Using a dynamic two-country two-commodity Ricardian model where preference for money (or wealth) leads to aggregate demand deficiency, this paper examines the relationship between the two countries' relative population size and their specialization patterns, employment and consumption. When the countries have similar population sizes, they specialize in respective commodities with comparative advantage. In this case a larger foreign, or a smaller home, population raises the relative price of the home commodity. It raises home real income and consumption per capita if full employment prevails in the home country. If unemployment appears, however, home employment and consumption per capita decrease.
Keywords: F41; E24; E32; 330; secular demand stagnation; liquidity trap; unemployment; population; specialization pattern